PREPARING TO TEACH OUR CHILDREN THE FOUNDATIONS FOR AN ANISHINAABE CURRICULUM - Anderson, Waabginojii / David (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2002)
ABSTRACT. The current generation of students has not learned Anishinaabe traditions; students have not been taught in an Anishinaabe context. They are proficient only in the language of the colonizer. In honour of our Grandfathers and Grandmothers who maintained our languages and our traditions, it is up to us to develop a curriculum that respects our Teachings and enables our children to remain Anishinaabe into the 21st century. The lessons of seven generations before us will prepare us for seven generations after us. This paper outlines mookise, the new beginning. COMMENT SE PRÉPARER À ÉDUQUER NOS ENFANTS DANS LES FONDEMENTS D’UN PROGRAMME D’ÉTUDES ANISHINAABE RÉSUMÉ. L’actuelle génération d’étudiants n’a pas appris nos traditions anishinaabe; ils n’ont pas suivi leur programme d’études dans un contexte anishinaabe. Ils ne connaissent que la langue du colonisateur. Pour rendre honneur à nos grands-pères et à nos grands-mères qui ont préservé nos langues et nos traditions, c’est à nous qu’incombe la tâche d’élaborer un programme d’études qui respecte nos enseignements et qui permette à nos enfants de rester anishinaabe au XXle siècle. Les leçons des sept générations qui nous ont précédés nous prépareront pour les sept générations qui nous suivront. Cet article souligne le processus, Mookise.